Vocational Education, Skill Formation, and Social Development - Haisheng Pan; Geng Wang; Wenjuan Gao; Xinqiao Liu (Education Sciences)
Vocational education plays a crucial role in cultivating high-quality skilled professionals to meet the demands of social development and is intrinsically linked to industrial upgrading [...]